Attitudes towards COVID-19 as predictors of emotional exhaustion in university students from a higher education center in the city of Chiclayo - Alfaro-Bustamante, Oscar; Alberto, Vicuña Peri, Luis; Loza, Miryam Griselda Lora (Edelweiss Applied Science and Technology, 2025)
The recent health crisis has significantly affected the mental health of college students, with emotional exhaustion being the most prominent issue. This study seeks to determine how attitudes toward the health crisis predict emotional exhaustion in university students. A quantitative methodology with a cross-sectional design and correlational-causal scope was used. The sample, which was representative and randomly selected, included 297 university students. A validated questionnaire was used to assess attitudes toward the health crisis, and a scale was used to measure emotional exhaustion, with inclusion criteria that considered voluntary participation and informed consent. The results of linear regression analysis indicated that attitudes toward the health crisis (β = -0.203, p < 0.001) and the emotional-affective dimension (β = -0.290, p < 0.001) are significant predictors of emotional exhaustion. However, the behavioral (β = -0.096, p = 0.098) and cognitive (β = -0.106, p = 0.069) dimensions did not show a statistically significant relationship. In conclusion, negative attitudes toward the health crisis, especially in the emotional-affective domain, increase the risk of emotional exhaustion in university students, underscoring the need for interventions that address these attitudes to improve students’ emotional well-being.